Stylistic Foregrounding in The Socio-Political Commentary of Selected Guardian Cartoons - Omolade Bamigboye; Samuel Adebayo Omotunde (Journal of Language and Literature, 2019)
The paper investigates the role of textual foregrounding in the understanding of cartoons in The Guardian, a Nigerian daily newspaper. To achieve this aim, Ballys stylistics of humor is used as theoretical basis. Ballys theory claims that there is a connection between language and the thoughts and feelings of its user. It also espouses the idea that as human beings, we respond emotionally in one way or the other to how a language is crafted in a particular context and by a particular user. This is especially the case for structures that are deemed humorous. Using a purposive data selection method, selected cartoon pieces from The Guardian about the 2015 general elections in Nigeria were collated, with a view to subjecting them to stylistic investigation. The eight selected cartoons are analyzed methodically, bringing out the stylistic use of foregrounding by the cartoonists. Findings reveal that through a shared body of world knowledge and current affairs, the cartoonist and his audience communicate via the short, witty and didactic cartoons in the overall interest of probity, decency, and accountability in the Nigerian public place. The artist highlights sensitive information he wishes to emphasize, by bringing such to the fore, through foregrounding. The conclusion and contribution to existing literature is that textual foregrounding, as a stylistic tool, is of immeasurable importance to the cartoonist in the daily execution of his art.